The contradictions of pop nationalism in the manga gate: Thus the JSDF fought there! - Martin, Paul (Taylor & Francis, 2018)
Though Japan’s post-war constitution forbids maintaining the means of waging war, the Japanese Self-Defence Force (JSDF) is one of the most powerful militaries in the world. This contradiction has become increasingly important in recent years as the JSDF has expanded its role and public profile, and as the state has moved closer to re-writing the constitution to allow for a more robust military policy. Alongside this military contradiction is a nationalistic one. The hyper-nationalism of the Pacific War left a general suspicion of overt nationalism amongst Japan’s population, but in recent years casual forms of nationalism have emerged that decouple pride in national identity from political commitment. This article focuses on the manga Gate: Thus the JSDF Fought There! to unpack the relationship between nationalism and the JSDF’s ambiguous position. In this manga, Japan is invaded through a mysterious portal from a fantasy world, allowing the manga to depict the JSDF in combat. While the manga hews close to official JSDF self-representations, in attempting to show the JSDF at war, the manga’s images, characters and narrative foreground contradictions inherent in the JSDF and in Japanese forms of nationalism.